Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(A=5xy-3,5y^2-2xy+1,3xy+3x-2y\)
\(=\left(5xy-2xy+1,3xy\right)-3,5y^2+3x-2y\)
\(=-3,5y^2+4,3xy+3x-2y\)
b) \(B=\dfrac{1}{2}ab^2-\dfrac{7}{8}ab^2+\dfrac{3}{4}a^2b-\dfrac{3}{8}a^2b-\dfrac{1}{2}ab^2\)
\(=\left(\dfrac{1}{2}ab^2-\dfrac{7}{8}ab^2-\dfrac{1}{2}ab^2\right)+\left(\dfrac{3}{4}a^2b-\dfrac{3}{8}a^2b\right)\)
\(=-\dfrac{7}{8}ab^2+\dfrac{3}{8}a^2b\)
c) \(2a^2b-8b^2+5a^2b+5c^2-3b^2+4c^2\)
\(=\left(2a^2b+5a^2b\right)+\left(-8b^2-3b^2\right)+\left(5c^2+4c^2\right)\)
\(=7a^2b-11b^2+9c^2\)
a: \(A=\left(5xy-2xy+1.3xy\right)+3x-2y-3.5y^2\)
\(=4.3xy+3x-2y-3.5y^2\)
b: \(B=\left(\dfrac{1}{2}ab^2-\dfrac{1}{2}ab^2-\dfrac{7}{8}ab^2\right)+\left(\dfrac{3}{4}a^2b-\dfrac{3}{8}a^2b\right)\)
\(=-\dfrac{7}{8}ab^2+\dfrac{3}{8}a^2b\)
c: \(C=\left(2a^2b+5a^2b\right)+\left(-8b^2-3b^2\right)+\left(5c^2+4c^2\right)\)
\(=7a^2b-11b^2+9c^2\)
a: \(=\left(15x^2y^3-12x^2y^3\right)+\left(7x^2-12x^2\right)+\left(-8x^3y^2+11x^3y^2\right)\)
\(=3x^2y^3-5x^2+3x^3y^2\)
bậc là 5
b: \(=\left(3x^5y-\dfrac{1}{2}x^5y\right)+\left(\dfrac{1}{3}xy^4+2xy^4\right)+\left(\dfrac{3}{4}x^2y^3-x^2y^3\right)\)
\(=\dfrac{5}{2}x^5y+\dfrac{7}{3}xy^4-\dfrac{1}{4}x^2y^3\)
Bậc là 6
c: \(=5xy-2xy+4xy-y^2+3x-2y\)
\(=-y^2+3x-2y+7xy\)
Bậc là 2
i) Đặt \(\frac{a}{2}=\frac{b}{3}=\frac{c}{4}=k\Rightarrow\begin{cases}a=2k\\b=3k\\c=4k\end{cases}\)
Vì a3 + b3 + c3 = 792 => 8k3 + 27k3 + 64k3 = 792 => 99k3 = 792 => k3 = 8 => k = 2
=> \(\begin{cases}a=4\\b=6\\c=8\end{cases}\)
Bài g tương tự bài i
e) Từ 3a = 7b => \(\frac{a}{7}=\frac{b}{3}\)
Đặt \(k=\frac{a}{7}=\frac{b}{3}\Rightarrow\begin{cases}a=7k\\b=3k\end{cases}\)
Vì a2 - b2 = 160 => 49k2 - 9k2 = 160 => 40k2 = 160 => k = 2 hoặc -2
Với k = 2 => \(\begin{cases}a=14\\b=6\end{cases}\)
Với k = -2 => \(\begin{cases}a=-14\\b=-6\end{cases}\)
A=\(\left(-\frac{5}{4}\times\frac{2}{5}\right)\times\left(x^3x^2x^3\right)\times\left(yy^4\right)\)
A=\(-\frac{1}{2}x^8y^5\)
B=\(\left(-\frac{3}{4}\times-\frac{8}{9}\right)\times\left(x^5xx^2\right)\times\left(y^4y^2y^5\right)\)
B=\(\frac{2}{3}x^8y^{11}\)
A=\(x^3.\left(\frac{-5}{4}x^2y\right)\)=\(x^5\).\(\left(\frac{-5}{4}\right)y\)
-Bậc là: 6
-Hệ số:\(\frac{-5}{4}\)
B=\(\left(\frac{-3}{4}x^5y^4\right).\left(xy^2\right).\left(\frac{-8}{9}\right)\)\(x^2y^5\)
=\(\frac{2}{3}.x^8.y^{11}\)
-Bậc là: 19
-Hệ số:\(\frac{2}{3}\)
C=\(\frac{1}{6}x\left(2y^3\right)^2.\left(-9x^5y\right)\)
=\(\frac{1}{6}x\left(4.y^6\right).\left(-9x^5y\right)\)
=-6.\(x^6\).\(y^7\)
-Bậc là: 13
-Hệ số: -6
sai het roi cung oi